Survival of high viscosity ionomers in molars with atraumatic restoration treatment in preschool children, one year of follow-up. - Carla Zúñiga Salas (2020)
OBJECTIVE: to evaluate the survival of high viscosity ionomers in molars with atraumatic restoration treatment at 3, 6, 9 and 12 months. MATERIAL AND METHODS: it was an interventional, observational and longitudinal study. Of 100 preschoolers of both sexes from a rural public school, the 30 preschoolers selected met the inclusion criteria; their parents agreed to sign the consent. The university UCSM gave the approval of the Ethics Committee with the number 2017-07. A USP senior pediatric dentist calibrated three pediatric dentists to unify the criteria of ionomer manipulation and atraumatic restoration treatment standardized by WHO, 12 with intra-specialist Kappa 0.9 and inter-specialist Kappa 0.8. The ionomers for the clinical technique were applied in 143 deciduous molars that met the inclusion criteria, the retention and survival of the ionomers were evaluated according to the criteria established by Frencken and Holgren7 at 3, 6, 9 and 12 months. We used the statistical package SSPS version 23. RESULTS: the ionomers remain in good condition at 3 months 97.9%, at 6 months 96.5%, at 9 months 94.4% and at 12 months 85.3%. The survival of the ionomers and the type of simple cavity was significant (p 0.05 Mc Nemar and ANOVA). The Kaplan Meier survival analysis determined the clinical changes of glass ionomers. CONCLUSION: The average survival of ionomers in molars with atraumatic restoration treatment was 11.22 months, considered high with greater permanence of the ionomers in simple cavities compared to the composite ones. In the results, the calibration of the researchers in the manipulation of the ionomers and in the application of the standardized clinical technique was decisive.